GC-MS-based fecal metabolomics reveals gender-attributed fecal signatures in ankylosing spondylitis - He, Zhixing (Sci Rep, 2019)
Ankylosing spondylitis (AS) has different clinical features in males and females. Fecal metabolites play significant roles in AS disorders. This study aimed to reveal gender-attributed fecal signatures of AS. Fecal samples from 87 cross-sectional individuals (healthy controls: 20 males, 18 females; AS patients: 26 males, 23 females) were analyzed by gas chromatography-mass spectroscopy (GC-MS). Partial least squares discriminant analysis (PLS-DA) was used to reveal differences in the fecal signatures of AS between males and females. Fecal signatures were defined by the significantly different fecal metabolites between AS patients and healthy individuals. Therefore, different fecal signatures of male and female AS patients were defined as gender-attributed fecal signatures. Male-specific fecal signatures in AS patients were steroid compounds, including cholestan-3-ol, tocopherol, stigmastan-3,5-diene, cholest-3-ene, cholest-4-en-6-one and 1-heptatriacotanol. Female-specific fecal signatures were ergost-5-en-3-ol, acetate and D-myo-Inositol. Gender-attributed fecal signatures of AS further reveal differences between males and females in terms of AS features.